The emerging role of apolipoprotein C-III: beyond effects on triglyceride metabolism. Issue 1 (December 2016) - Luo, Mengdie; Peng, Daoquan
Abstract Apolipoprotein C-III has been referred to as an important participant in the metabolism of triglyceride-rich lipoproteins, leading to hypertriglyceridemia and thereafter cardiovascular disease. Accumulating evidence indicates that apolipoprotein C-III is a multifaceted protein which not only regulates triglyceride metabolism, but also participates in the atherosclerotic lesion formation and several other pathological processes involved in atherosclerosis. Based on data from experiments and clinical trials, some novel therapies such as antisense technology emerge.